The Application of Adaptive Backstepping Sliding Mode for Hybrid Humanoid Robot Arm Trajectory Tracking Control - Li Qin; Fucai Liu; Lihuan Liang (Advances in Mechanical Engineering, 2014)
This paper presents a methodology of the dynamic analysis and control for a novel hybrid humanoid robot arm. The hybrid humanoid robot arm under consideration consists of a spherical parallel manipulator (SPM) connecting two revolute pairs in series form. The dynamic model of the hybrid humanoid robot arm has been set up based on the Lie group and Lie algebra combined with the principle of virtual work, which can avoid the processing of constraint reaction and the division of logic open chains, as well as a great quantity of differential operation. Aiming at the parameter uncertainties and disturbances, an adaptive backstepping sliding mode controller is developed. Compared with PD control in trajectory tracking simulation, the results show the advantage of the controller.